Dampak Pemali terhadap Disiplin Hidup dan Implikasinya bagi Iman Umat Suku Pinue - adminjurnal, adminjurnal (JURNAL PROPHETA, 2022)
he aim of this research is to understand the development of community life and all behavior that exists in a society. Data is collected through interviews, observations, documentation studies where the researcher is the key instrument. The data collection technique was carried out using triangulation (combination), data analysis was inductive, and the results of qualitative research emphasized meaning rather than generalization. The results of research in the field prove that as a prospective catechist, everyone is a believer who proclaims the Good News and the Kingdom of God through the testimony of life and words. Students are called to develop God's mission in the world, whether at school or at the grassroots and elsewhere. As a prospective catechist who later becomes a catechist, he develops the obligation and right to continuously fight for the message of salvation that reaches all nations and transcends all ages. Therefore, character education which is carried out in the community of Fafinesu B Village, especially the Pineul Tribe, is very important and has benefits for every student. By being guided by Jesus Christ as a figure who can be emulated, a student who will be a role model must be able to do good manners, obey discipline, and forgive a lot in the practice of daily life.